Comparison of semicircular and bent tips regarding regional differences in oscillation amplitude under various torsional power settings. Issue 10 (October 2020) - Noguchi, Santaro; Baba, Koichi; Maeda, Naoyuki; Oie, Yoshinori; Nakakura, Shunsuke; Tabuchi, Hitoshi; Nishida, Kohji
Abstract : The amplitude of torsional phacoemulsification tip does not increase proportionally on reaching the upper limit. The balanced tip might cause damage to wound tissues inserting at approximately 3 mm. Abstract : Purpose: To analyze the difference between the behavior of semicircular (balanced) and bent (mini) tips at 20 incremental torsional power settings. Setting: Tsukazaki Hospital, Himeji, Japan. Design: Experimental study. Methods: Using an ultra-high-speed video camera HPV-X2, the 2 tips during torsional oscillation were recorded, comparing tip behavior at power settings from 5% to 100% by tracking points 1 to 5 (tip end and at 1325, 2650, 3975, and 5035 μm from the tip end). Results: Both tips increased their amplitude widths, drawing an S-curve at all points as the torsional power setting was increased, reaching their upper limits from 70% to 90% torsional power. At all 20 power settings, both tips showed significantly different amplitudes (all P < .01), and the difference of the amplitude increased as the power setting increased. Although, at points 1 and 3, the balanced tip amplitude was nearly 1.5 times larger than the mini tip amplitude, the amplitude difference was 10 μm or less at points 2 and 4. At point 5, the mini tip amplitude was at least 3 times more than the balanced tip amplitude. Conclusions: The amplitude does not increase proportionally and varies markedly with the tip shape on reaching the upper limit, suggesting that a higher power setting might not contribute greatly to nuclear fragmentation. The balanced tip might cause greater damage to surrounding tissues if it is inserted at approximately 3 mm from the wound site. To obtain maximum shaft stability using the balanced tip, it is important to insert at least 5 mm.